Suppliers selection problem with quantity discounts and price changes: a heuristic approach - Rodrigues, Filipe (2020)
This paper addresses a complex suppliers selection problem with multiple products, considering minimum package quantities, minimum order values related to delivery costs and discounted pricing schemes. Its main contribution is to present an integer linear programming (ILP) model for this suppliers selection problem as well as a model to analyse the impact of prices change. Furthermore, a hybrid heuristic and a genetic algorithm to obtain feasible solutions for this problem are presented. Several randomly generated examples are solved by using the above two models and the heuristic approaches. Experimental results demonstrate the robustness of the genetic algorithm and allow to realize which are the most important decisions in the suppliers selection problem.